LATE GLACIAL AND HOLOCENE BIOCLIMATIC RECONSTRUCTION IN SOUTHERN ITALY: THE TRIFOGLIETTI LAKE - Brugiapaglia, E.; de Beaulieu, J.-L.; Guiter, F.; Joannin, S.; Magny, M.; Peyron, O.; Didier, J.; Stock, A.; Zanchetta, G. (Annali di Botanica, 2013)
The pollen record from Trifoglietti lake (Calabria region) provides new information about the paleoenvironmental and palaeoclimatic changes occurred during the LateGlacial and Holocene period. The LateGlacial part of the record, for which only preliminary data is available, is a new and original sequence from southern Italy. The Holocene sequence, with 11 AMS radiocarbon dates shows a stable Fagus forest for the entire period. Apart from sporadic pastoralism activities and the selective exploitation of Abies, only a weak human impact is recognized in the pollen records. Lake level oscillations have been reconstructed and annual precipitations quantified using the Modern Analogue Technique. The reconstruction was effectuated both at millennial and centennial scale: the first shows an increasing of moisture from 11000 to 9400 cal BP and a maximum of humidity from 9400 to 6200 cal BP. Moreover, several climatic oscillations punctuated the Holocene and therefore superimposed the millennial trend.